Concerning Preventive Vaccination, Infectious Diseases and the Extent of Responsibility - S. V. Ilina (Педиатрическая фармакология)
Despite the huge and seamingly undisputable success of vaccinal prevention, a critical situation is developing today in the context of immunization-controlled infections control. Increasing antivaccination propahanda leads to a decrease in the collective immunity and the occurance of high-contagenous infectious diseases in various places of the world. It is a disturbing tendency — the usage of antivaccinal ideas for populist purposes. This article contains several examples of how such tactics lead to severe consequences for public health: pertussis and morbilli epidemia in Europe, poliomyelitis epidemia in African and Asian countries.